The semantics of the word “dispute” based on the seven types of Izutsu's simultaneous semantic theory - Sakineh Mosavi Asl; Shaker Ameri; Ali akbar Noresideh (مطالعات زبانی و بلاغی)
Discovering and investigating the "relative" meaning of key words in the context of Quranic verses is emphasized by the theory of simultaneous semantics. In Izutsu's Quranic thought, a key word can have two basic and relative meanings; but the meaning of "relative" should provide a clearer picture of it in the semantic system of the Qur'an. The word "dispute" is one of the key concepts of the Quran. In this research, an attempt has been made to present a more precise concept of “dispute” by relying on the seven methods of simultaneous semantics in an analytical-descriptive manner. These seven methods are textual definition, finding synonyms (substitutes), finding antonyms, balancing the grammatical structure (synonyms) of sentences, forming semantic fields, negative form of words and application in non-religious context. Based on the findings of this research, it was concluded that the word "dispute" in the Quran is used both positively (dispute with goodness/dispute with truth) and negatively (dispute with unrighteousness/dispute with falsehood). However, as a focal term, the word is more frequently used in its negative sense. The relative meaning of "right dispute" in the Qur'an is a struggle that takes place with tools such as Sultan, knowledge, guidance, benefiting from the teachings of the holy books, wisdom, good preaching, etc. In the relative concept of "false dispute", disbelief is considered the most obvious feature of dispute. Argumentative person refuses to accept the divine revelations despite the truth being presented, and with the aim of destroying the truth, starts fighting against it. The source of dispute comprises several factors such as pride, lack of knowledge and authority, obedience to the temptation of devils, following the wrong tradition of the predecessors, and the result is misguidance, mockery of the verses, oppression, immorality, polytheism, etc. In addition, in a relative sense, emphasis is placed on the continuous and dominant flow of false dispute on the society and the ominous outcome of the disputants.